Strategi Mitigasi Risiko Untuk Meningkatkan Efektivitas Pengelolaan Sekolah - Ramadhan, Fadila (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This study aims to describe the concept of risk management and mitigation strategies that can be applied in school management to improve the effectiveness of education delivery. The research method used is library research by analyzing various literature sources such as books and relevant scientific journals. The results of the study indicate that risk management in schools is a systematic process that includes the identification, assessment, and control of various potential threats that can hinder the achievement of educational goals. Risks faced by schools can originate from operational, financial, human resources, environmental, and institutional reputation aspects. To reduce the negative impact of these risks, schools need to implement mitigation strategies such as avoiding, reducing, transferring, or accepting risks with careful planning. The implementation of appropriate risk mitigation strategies not only functions as a preventative measure against problems, but also as a strategic step in creating a safe, efficient, and sustainable learning environment. Thus, effective risk management is an important part of improving the quality and stability of school management.